Cortical activation and functional connectivity during locomotion tasks in Parkinson’s disease with freezing of gait - Feng, HongSheng; Jiang, YanNa; Lin, JinPeng; Qin, WenTing; Jin, LingJing; Shen, Xia (Frontiers in Aging Neuroscience, 2023)
Background Freezing of gait (FoG) is a severely disabling symptom in Parkinson’s disease (PD). The cortical mechanisms underlying FoG during locomotion tasks have rarely been investigated. Objectives We aimed to compare the cerebral haemodynamic response during FoG-prone locomotion tasks in patients with PD and FoG (PD-FoG), patients with PD but without FoG (PD-nFoG), and healthy controls (HCs). Methods Twelve PD-FoG patients, 10 PD-nFoG patients, and 12 HCs were included in the study. Locomotion tasks included normal stepping, normal turning and fast turning ranked as three difficulty levels based on kinematic requirements and probability of provoking FoG. During each task, we used functional near-infrared spectroscopy to capture concentration changes of oxygenated haemoglobin (ΔHBO2) and deoxygenated haemoglobin (ΔHHB) that reflected cortical activation, and recorded task performance time. The cortical regions of interest (ROIs) were prefrontal cortex (PFC), supplementary motor area (SMA), premotor cortex (PMC), and sensorimotor cortex (SMC). Intra-cortical functional connectivity during each task was estimated based on correlation of ΔHBO2 between ROIs. Two-way multivariate ANOVA with task performance time as a covariate was conducted to investigate task and group effects on cerebral haemodynamic responses of ROIs. Z statistics of z-scored connectivity between ROIs were used to determine task and group effects on functional connectivity. Results PD-FoG patients spent a nearly significant longer time completing locomotion tasks than PD-nFoG patients. Compared with PD-nFoG patients, they showed weaker activation (less ΔHBO2) in the PFC and PMC. Compared with HCs, they had comparable ΔHBO2 in all ROIs but more negative ΔHHB in the SMC, whereas PD-nFoG showed SMA and PMC hyperactivity but more negative ΔHHB in the SMC. With increased task difficulty, ΔHBO2 increased in each ROI except in the PFC. Regarding functional connectivity during normal stepping, PD-FoG patients showed positive and strong PFC-PMC connectivity, in contrast to the negative PFC-PMC connectivity observed in HCs. They also had greater PFC-SMC connectivity than the other groups. However, they exhibited decreased SMA-SMC connectivity when task difficulty increased and had lower SMA-PMC connectivity than HCs during fast turning. Conclusion Insufficient compensatory cortical activation and depletion of functional connectivity during complex locomotion in PD-FoG patients could be potential mechanisms underlying FoG. Clinical trial registration Chinese clinical trial registry (URL: http://www.chictr.org.cn, registration number: ChiCTR2100042813).